Application of the Prague C and M criteria for endoscopic description of columnar-lined esophagus in South Korea - Choe, Jung Wan (World J Gastrointest Endosc, 2016)
AIM: To ascertain whether the Prague circumferential (C) length and maximal (M) length criteria for grading the extent of Barrett’s esophagus can be applied prior to its widespread application in South Korea. METHODS: Two hundred and thirteen consecutive cases with endoscopic columnar-lined esophagus (CLE) were included and classified according to the Prague C and M criteria. RESULTS: Of 213 cases with CLE, the distribution of maximum CLE lengths was: 0.5-0.9 cm in 99 cases (46.5%); 1.0-1.4 cm in 63 cases (29.6%); 1.5-1.9 cm in 15 cases (7.0%); 2.0-2.4 cm in 14 cases (6.6%); 2.5-2.9 cm in 1 case (0.5%); and 7.0 cm in 1 case (0.5%). Twenty cases (9.4%) had columnar islands alone. Two hundred and eight cases (97.7%) lacked the circumferential CLE component (C0Mx). Columnar islands were found in 70 cases (32.9%), of which 20 cases (9.4%) had columnar islands alone. CONCLUSION: In regions where most CLE patients display short or ultrashort tongue-like appearance, more detailed descriptions of CLE’s in < 1.0 cm lengths and columnar islands, as well as avoidance of repeating the prefix “C0” need to be considered in parallel with the widespread application of the Prague system in South Korea.